2019
DOI: 10.1097/mcg.0000000000001233
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nano Vitamin D Supplementation Reduces Disease Activity in Ulcerative Colitis

Abstract: Introduction: Vitamin D possesses anti-inflammatory properties and could be beneficial in ulcerative colitis (UC). Methods: We studied the effect of oral nano vitamin D3 supplementation on disease activity in active UC [ulcerative colitis disease activity index (UCDAI)≥3]. Patients with active UC and vitamin D <40 ng/mL were randomized to receive either oral nano vitamin D (60,000 IU/d×8 d) or placebo. They were evaluated for disease activity (UCDAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…In conclusion, here we report that patients taking vitamin D at the time their first ICI treatment was initiated had significantly reduced odds of developing ICI colitis over the course of their immunotherapy regimen. These results may suggest benefit in prophylactic use of vitamin D supplementation to prevent ICI colitis, as previously demonstrated in inflammatory bowel disease [56][57][58][59]65,66 and graft-versus-host disease. 49,67,68 Cancer August 15, 2020…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In conclusion, here we report that patients taking vitamin D at the time their first ICI treatment was initiated had significantly reduced odds of developing ICI colitis over the course of their immunotherapy regimen. These results may suggest benefit in prophylactic use of vitamin D supplementation to prevent ICI colitis, as previously demonstrated in inflammatory bowel disease [56][57][58][59]65,66 and graft-versus-host disease. 49,67,68 Cancer August 15, 2020…”
Section: Discussionsupporting
confidence: 75%
“…55 There is growing evidence that vitamin D supplementation reduces disease severity and risk of relapse in IBD patients. [56][57][58][59] In the multivariable regression model of our discovery cohort, we also found that elevated baseline NLR ≥ 5 was negatively correlated with risk of developing ICI colitis. This finding is similar to that of a recent study in South Korea reporting lower risk of irAEs in patients with baseline NLR ≥ 3 who were treated with pembrolizumab, although this study did not examine colitis specifically.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In many epidemiological studies, it is stated that there is a relationship between vitamin D3 levels and the life quality of IBD patients 22 . It has been observed that supplementing vitamin D in patients with active UC with low level of vitamin D decreases the clinical activity of the disease, decreases the levels of inflammation markers and improves histopathological alterations 24 . Vitamin D plays a role in cell proliferation and differentiation, as well as immunomodulation 25,26 .…”
Section: ■ Resultsmentioning
confidence: 99%